2021
DOI: 10.1038/s41598-021-81013-0
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous determination of spirodiclofen, spiromesifen, and spirotetramat and their relevant metabolites in edible fungi using ultra-performance liquid chromatography/tandem mass spectrometry

Abstract: A fast, sensitive, and reliable analytical method was developed and validated for simultaneous identification and quantification of spirodiclofen, spiromesifen, and spirotetramat and their relevant metabolites in edible fungi by ultra-performance liquid chromatography/tandem mass spectrometry (UHPLC–MS/MS). First, sample extraction was done with acetonitrile containing 1% formic acid followed by phase separation with the addition of MgSO4:NaOAc. Then, the supernatant was purified by primary secondary amine (PS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 30 publications
(47 reference statements)
0
3
0
Order By: Relevance
“…In addition to PSA, C18, and GCB used in this study, some other adsorbents used for removing specific compounds also showed good purification effects. For example, the new materials EMR-lipid and LM806-FC-722 were applied to remove the fatty acids, lipids, and pigments from edible fungi . The results demonstrated that recovery and RSD were both satisfied when 20 mg of PSA + 30 mg of C18 and LM806-FC-722 were used in Pleurotus ostreatus.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to PSA, C18, and GCB used in this study, some other adsorbents used for removing specific compounds also showed good purification effects. For example, the new materials EMR-lipid and LM806-FC-722 were applied to remove the fatty acids, lipids, and pigments from edible fungi . The results demonstrated that recovery and RSD were both satisfied when 20 mg of PSA + 30 mg of C18 and LM806-FC-722 were used in Pleurotus ostreatus.…”
Section: Resultsmentioning
confidence: 99%
“…For example, the new materials EMR-lipid and LM806-FC-722 were applied to remove the fatty acids, lipids, and pigments from edible fungi. 33 The results demonstrated that recovery and RSD were both satisfied when 20 mg of PSA + 30 mg of C18 and LM806-FC-722 were used in Pleurotus ostreatus. Meanwhile, 20 mg of PSA + 30 mg of C18 and EMR-lipid as sorbents were used in Flammulina velutiper, and the recoveries were satisfactory.…”
Section: Optimization Of Cleanup Sorbentsmentioning
confidence: 88%
“…Spiromesifen is the most recently developed class of acaricides. These acaricides act as an acetyl-coenzyme A carboxylase (ACCase) inhibitor by interfering with lipid biosynthesis [5]. Etoxazole is a 2,4-diphenylthiazole derivative compound that can inhibit the embryonic formation of mite eggs and the molting process from larvae to adults.…”
Section: Introductionmentioning
confidence: 99%